Peran Literasi Kewarganegaraan Digital dalam Menangkal Polarisasi Politik di Ruang Publik Virtual - Ahmad Zulkarnain Effendi; Siti Fatimah Rahayu; Muhammad Ikhsanuddin Pratama (PT. Panca Publishing Indonesia, 2026)
This study investigates the role of digital civic literacy in countering political polarization in virtual public spaces in Indonesia. The background stems from the rapid spread of political misinformation and identity-based division intensified through social media platforms, particularly during electoral periods. The purpose is to analyze how digital civic literacy competencies function as a protective factor against polarizing narratives and to identify effective strategies for its development. Employing a qualitative approach through critical discourse analysis and library research, this study examines relevant policy documents, academic literature, and digital literacy program reports published between 2020 and 2024. Findings reveal that digital civic literacy encompassing critical information evaluation, democratic participation ethics, and intergroup empathy significantly reduces susceptibility to polarizing content. The study concludes that systematic integration of digital civic literacy into formal education and community programs is essential for sustaining democratic resilience in Indonesia's digital public sphere.